# Why is my code not working?

조회 수: 2(최근 30일)
Michael Vaughan 2020년 9월 26일
답변: Jim Riggs 2020년 9월 26일
I want the following script to calculate:
$$J_{(2,k)}(N)=\frac{1}{s-s^{-1}}{\sum_{j=\frac{-(N-1)}{2}}^{\frac{(N-1)}{2}}(s^{4j^2k+2jk}s^{4j+1}-s^{4r^2k-2jk}s^{4j-1})}$$
function f = CJ(N,k)
syms t
% compute the running sum
running_sum = 0;
for j = -(N-1)/2:(N-1)/2
running_sum = running_sum + t^(4*j^2*k+2*j*k)*t^(4*j+1)-t^(4*j^2*k-2*j*k)*t^(4*j-1);
end
% final value
f = (1/(t-t^(-1))*running_sum
end
Here is what happens when I try to run the program:
>> CJ(3,2)
Error: File: CJ.m Line: 10 Column: 34
Invalid expression. When calling a function or indexing a variable, use parentheses. Otherwise, check for mismatched
delimiters.

댓글을 달려면 로그인하십시오.

### 답변(1개)

Jim Riggs 2020년 9월 26일
Not entirely sure if this is the reference in the error message, but this line has unballanced parentheses:
f = (1/(t-t^(-1))*running_sum

댓글을 달려면 로그인하십시오.

### Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!

Translated by